Analisis Usability pada Website WaralabaKita Menggunakan Metode System Usability Scale - Chandra, Daniel Kevin; Rahman, Syaiful; Surasa, Hendra (KHARISMA Tech, 2023)
This study aims to analyze the Usability of the WaralabaKita website based on user respondents using the System Usability Scale method. The main key of assessing this method is Utility, whether it is in accordance with user needs. This study used a questionnaire as a means of data collection, then continued by testing the validity of the data to analyze data from 10 questions which resulted in Cronbach's Alpha value of 0.637. From the 30 samples that have been collected, an average SUS score of 69.17 was obtained, which means that this score was included in the Marginal High category and classified into the OK category.